An ensign to the nations. (The Church of Jesus Christ of Latter-Day Saints, 1997)
Four yeard after the church was organized, the Prophet Joseph Smith met in a small log schoolhouse with priesthood holders in Kirtland, Ohio, and said: Brethen ... you know no more concerning the destinies of this Church and kongdom than a babe upon its mother's lap. You don't comprehend it ... it is only a little handful of Priesthood you see here tonight, but this Church will fill North and South America-it will fill the world (Wilford Eoodruff, in Conference Report, Apr. 1898, 57).